Question 50: Performing the calculation (frac{5}{6} + frac{1}{4} ) we get the result: A. (frac{{13}}{{12}}) B. (frac{{1}}{{12}}) C. (frac{{7}}{{12}}) D. (frac{{11}}{{12}}) We have (frac{5}{6} + frac{1}{4} = frac{{20}}{{24}} + frac{6}{{24}} = frac{{20 + 6}}{{24}} = frac{{26}}{{24}} = frac{{13}}{{12}}) ===============

## Related Posts

### Spider-Man’s Tom Holland taking internet break as trolls send him ‘spiralling’

break, Holland, Internet, send, SpiderMans, spiralling, Tom, Trolls / 08/15/2022 08/15/2022